Preparation of Fe3O4 @ CaP magnetic fiber scaffold with electrospining. Issue 2 (March 2021) - Teng, Yu; Zhang, Jinliang; Li, Yingjuan; Cai, Chuanxiong; Chen, Fuliang
Abstract: Fe3 O4 @CaP magnetic fiber scaffold is prepared with electrospining by compounding ferroferric oxide nanoparticles into the calcium phosphate ceramic. The composite scaffold combines the superparamagnetism of ferroferric oxide nanoparticles and the good biocompatibility and bone tissue guidance of calcium phosphate, and has a high specific surface area and provides a suitable regeneration space for bone tissue, which is expected to be used for biomedical field.